2016
DOI: 10.22159/ajpcr.2017.v10i1.14326
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical Study of Medicinal Plants Used in Traditional Medicine in the Province of Sidi Kacem, Morocco

Abstract: Objective: It's an ethnobotanical study to establish a floristic catalog of medicinal plants harvested from the province of Sidi Kacem (Morocco), which are used in traditional therapy for respiratory, digestive and skin infections Methods: We carried out a field survey using a questionnaire sent to 200 people spread over four studied areas, previously determined by stratified sampling techniques. This survey includes a section on the informant's therapeutic practices, and another on the varieties of plants use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…5 In Sidi Kacem, Morocco, the leaves of parsley (locally called Maadnous) are used as a decoction for infections of the skin and gastrointestinal tract, urolithiasis, kidney pain, and pyelonephritis. 6 Parsley is among the most popular plants used by local people for renal dysfunction in Morocco. 7 Another study from Morocco reported that decoction of parsley aerial parts is orally used for gastrointestinal infections and cardiovascular problems, especially hypertension, and allergies.…”
Section: ■ Ethnobotanymentioning
confidence: 99%
See 1 more Smart Citation
“…5 In Sidi Kacem, Morocco, the leaves of parsley (locally called Maadnous) are used as a decoction for infections of the skin and gastrointestinal tract, urolithiasis, kidney pain, and pyelonephritis. 6 Parsley is among the most popular plants used by local people for renal dysfunction in Morocco. 7 Another study from Morocco reported that decoction of parsley aerial parts is orally used for gastrointestinal infections and cardiovascular problems, especially hypertension, and allergies.…”
Section: ■ Ethnobotanymentioning
confidence: 99%
“…In the Zlatibor district of South-Western Serbia, parsley leaves and roots are used as an infusion for fluid retention, as well as ailments and infections of the urinary tract . In Sidi Kacem, Morocco, the leaves of parsley (locally called Maâdnous ) are used as a decoction for infections of the skin and gastrointestinal tract, urolithiasis, kidney pain, and pyelonephritis . Parsley is among the most popular plants used by local people for renal dysfunction in Morocco .…”
Section: Ethnobotanymentioning
confidence: 99%